(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
يهدف البحث إلى دراسة تأثير التخزين الطبيعي للتبوغ بهدف تخميرها طبيعياً في التركيب الكيميائي المرتبط بالصفات النوعية للأوراق الجافة، وإلى دراسة تأثير التخمير الاصطناعي "تحت حرارة ورطوبة نسبية محددتين" في ذلك التركيب. تمت متابعة التغيرات في أثناء ثلاث سنوات ضمن مستودعات المؤسسة العامة للتبغ في اللاذقية والقرداحة وحلب، وأظهرت النتائج تحسناً في نوعية التبوغ المخزنة لمدة عامين من خلال تحلل النشاء إلى سكريات، وزيادة في نسبة السكريات، ونقص في البروتين وفقد في النيكوتين، لكن حدث تراجع في النوعية بعد مرور 30 شهراً من التخزين، أما التخمير الاصطناعي فلم يكن فعالاً كفايةً في تحسين نوعية التبوغ. This research was aimed to study the effect of natural storage of tobacco, or natural "fermentation" on the chemical composition related to quality of leaves. It also studies the effect of artificial fermentation "under controlled temperature and relative humidity" on that composition. These changes were continued during 3 years in warehouses of General Company of Tobacco in Lattakia, Kordaha, and Aleppo. The results showed improvement in quality of stored tobacco for 2 years, associated with starch conversion to sugar, increase in sugar, reduction in proteins, loss of nicotine. However, a reduction in quality occurred after 30 months of storage. Finally, the artificial fermentation was not effective enough for improving tobacco quality.